POWER AND MADNESS: A FOUCAULDIAN ANALYSIS OF INSTITUTIONAL CONTROL IN SHUTTER ISLAND - Maharani, Dhea Gladys; Nirmalawati, Widya (Universitas Putera Batam, 2025)
This study examines Michel Foucault's theories on power and madness through the film Shutter Island, focusing on how institutional control shapes perceptions of sanity and insanity. Using Madness and Civilization as a theoretical framework, the research explores how psychiatric institutions define and regulate madness, creating